The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/cbm.97
|View full text |Cite
|
Sign up to set email alerts
|

A review of the role of the legal adviser in police stations

Abstract: This article undertakes a brief review of research concerning the frequency and the quality of legal advice provided in police stations in England and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Representation was also contracted out to independent personnel who are not necessarily fully trained legally and this can include former police officers. It was also shown that the quality of legal representation at the police station varies widely from very effective to ineffective and worst still adverse representation (McConville and Hodgson, 1993;Pearse and Gudjonsson, 1996;Ede and Shepherd, 2000). More recently, Pattenden and Skinns (2010) noted that the system has changed in that the police no longer put the suspect through to a legal advisor.…”
Section: The Devil Is In the Detailmentioning
confidence: 99%
“…Representation was also contracted out to independent personnel who are not necessarily fully trained legally and this can include former police officers. It was also shown that the quality of legal representation at the police station varies widely from very effective to ineffective and worst still adverse representation (McConville and Hodgson, 1993;Pearse and Gudjonsson, 1996;Ede and Shepherd, 2000). More recently, Pattenden and Skinns (2010) noted that the system has changed in that the police no longer put the suspect through to a legal advisor.…”
Section: The Devil Is In the Detailmentioning
confidence: 99%